The Effect of Hearing Loss on Novel Word Learning in Infant- and Adult-Directed Speech - Robertson, V. Susie (Ear Hear, 2017)
OBJECTIVES: Relatively little is known about how young children with hearing impairment (HI) learn novel words in infant- and adult- directed speech. Infant-directed speech (IDS) supports word learning in typically developing infants relative to adult-directed speech (ADS). This study examined how children with normal hearing (NH) and children with HI learn novel words in IDS and ADS. It was predicted that IDS would support novel word learning in both groups of children. In addition, children with HI were expected to be less proficient word learners as compared to their NH peers. DESIGN: A looking-while-listening paradigm was used to measure novel word learning in 16 children with sensorineural HI (age range 23.2–42.1 months) who wore either bilateral hearing aids (n = 10) or bilateral cochlear implants (n = 6) and 16 children with NH (age range 23.1–42.1 months) who were matched for gender, chronological age, and maternal education level. Two measures of word learning were assessed (accuracy and reaction time). Each child participated in two experiments approximately one week apart, one in IDS and one in ADS. RESULTS: Both groups successfully learned the novel words in both speech type conditions, as evidenced by children looking at the correct picture significantly above chance. As a group, children with NH outperformed children with HI in the novel word learning task, however there were no significant differences between performance on IDS vs ADS. More fine-grained time course analyses revealed that children with HI, and particularly children who use hearing aids, had more difficulty learning novel words in ADS, compared to children with NH. CONCLUSIONS: The pattern of results observed in the children with HI suggests that they may need extended support from clinicians and caregivers, through the use of IDS, during novel word learning. Future research should continue to focus on understanding the factors (e.g., device type and use, age of intervention, audibility, acoustic characteristics of input, etc.) that may influence word learning in children with HI in both IDS and ADS.